Makroekonomiczne uwarunkowania konsumpcji turystycznej w okresie przekształceń społeczno-gospodarczych w Polsce w latach 1990-2010 - Kryczka, Małgorzata (My University, 2014)
Celem artykułu jest określenie wpływu czynników makroekonomicznych na kształtowanie się poziomu konsumpcji turystycznej w Polsce. W badaniach empirycznych zastosowano statystyczną metodę regresji wielorakiej, wpisującą się w ekonometryczną analizę szeregów czasowych oraz badanie relacji kointegrujących. Przedmiotem analizy była zależność konsumpcji usług turystycznych od zmiennych makroekonomicznych. Analizy wykonano na podstawie danych publikowanych przez Główny Urząd Statystyczny oraz Instytut Turystyki za okres 1990–2010. Badania wykazały, iż na konsumpcję turystyczną wpływają następujące czynniki makroekonomiczne: stopa bezrobocia, wartość PKB na osobę oraz kurs USD. Stopa inflacji nie miała istotnego wpływu na objaśniane zmienne, a szereg czasowy okazał się niestacjonarny. Wzrost stopy bezrobocia wpływał na spadek aktywności turystycznej Polaków. Rosnący PKB na osobę powodował wyraźny wzrost poziomu uczestnictwa w wyjazdach zagranicznych. Niezależnie od wzrostu tego wskaźnika spadała częstotliwość wyjazdów zarówno krajowych, jak i zagranicznych. Wzrost kursu USD przekładał się na wzrost uczestnictwa w krajowych wyjazdach turystycznych. Wskaźniki makroekonomiczne nie miały wpływu na wysokość ponoszonych wydatków turystycznych. Artykuł prezentuje wyniki badań empirycznych.

Purpose. To identify the macro-economic determinants of changes in tourism consumption in Poland. Method. In the empirical studies, multiple regression analysis was applied. This method is inscribed into the econometric analysis of time series variables, which means testing stationarity, as well as studying cointegrating relations. The subject of analysis was the relationship between the tourism consumption and macro-economic variables. The analysis was based on the data published by the Central Statistical Office and the Institute of Tourism in 1990–2010. Findings. The research has shown that the following macro-economic factors have an impact on tourism consumption: unemployment rate, gross domestic product (GDP) per capita, and the dollar exchange rate. The inflation rate did not have any significant impact in this study and the time series variable proved unsteady. The increase in the unemployment rate caused a decrease in the Polish people’s tourist activity. Growing GDP per capita led to an increase in foreign travel, but to a decrease in domestic travel. Regardless of the unemployment rate, the frequency of both foreign and domestic travel have generally decreased. The high exchange rate of USD however, has had an impact on domestic travel. Macro-economic factors have had no impact on the level of tourism expenditure in Poland.
Macro-economic Determinants of Tourism Consumption in the Socio-Economic Transition in Poland in 1990-2010
Keywords: konsumpcja turystyczna; uczestnictwo w turystyce; wydatki turystyczne; determinanty; zmienne makroekonomiczne; tourism consumption; tourism activity; participation in tourism; tourist trips expenditures; determinants; macroeconomic variables